ISLAM DAN HAK AZASI MANUSIA - Sahliah Sahliah (TAQNIN: Jurnal Syariah dan Hukum, 2020)
Islam is a religion that is blessed by Allah. Islam regulates all rules in human life. Islam really respects basic human rights which are the rights that are obtained since humans are born. The aim of this research is to describe human rights in the perspective of Islam. This study used a library research and the techniques used in analyzing the data were data reduction, data presentation and data verification. The study finds out that in Islam, human rights have strong sources. The finding of this study can increase our understanding about human right seen from Islamic perspective.